Postcolonial studies after Foucault : Discourse, discipline, biopower, and governmentality as travelling concepts - Willaert, Thijs; Justus Liebig University Giessen (My University, 2012)
In the wake of Edward Said´s Orientalism, a substantial number of scholars have drawn on the work of Michel Foucault in their efforts to conceptualize both colonialism and the resistance against it. Postcolonial Studies After Foucault attempts to map this postcolonial engagement with Foucault, focusing on the use of four Foucauldian concepts in key postcolonial texts: "discourse", "discipline", "biopower", and "governmentality". Through a comparative analysis of the multiple meanings, functions, and effects of these concepts as they travel from one context into another, this study seeks to highlight the complex processes of transformation that underlie the recontextualization of these concepts. Moreover, by analyzing the patterns that appear in these transformations, Postcolonial Studies After Foucault aims to raise and address the question of whether the various postcolonial appropriations of Foucauldian concepts have given rise to a distinctively "Foucauldian" critique of colonial power, and how such a "Foucault Effect" relates to other conceptualizations and critiques of colonial power.
Postcolonial Studies nach Foucault : Diskurs, Disziplin, Biomacht und Gouvernementalität als Travelling Concepts
Keywords: Foucault; Postcolonial Studies; Disziplin; Biomacht; Gouvernementalität; Foucault; Postcolonial Studies; Discipline; Biopower; Governmentality; ddc:420